Exploring the Interplay between Interest, Religiosity, and Zakah - Ahmad Syifa Utama; Muhsin Arafat (ASFA Foundation, 2026)
Religiosity within the Islamic framework represents a key determinant in fulfilling religious duties, particularly in the practice of zakat. In Ponorogo Regency, although the potential zakat collection is projected to reach approximately IDR 590 billion annually, data from BAZNAS reveal that only about 3% of this amount has been realized. This research investigates how religiosity influences the willingness of traders to fulfill their zakat obligations through formal Amil Zakat Institutions (LAZ). Employing a quantitative research design, data were gathered using a structured questionnaire based on the Likert scale. A total of 75 respondents, drawn randomly from clothing traders at Songgo Langit Market, constituted the study sample. The analysis utilized simple linear regression to evaluate the relationship between the variables. Findings demonstrate that religiosity exerts a significant and positive impact on traders’ intention to pay zakat via LAZ, accounting for 22% of the variation, while the remaining 78% can be attributed to other determinants beyond the current model. These results highlight that, alongside religiosity, complementary strategies are necessary to strengthen both awareness and willingness to optimize zakat payments.